Impacts of considering climate variability on investment decisions in Ethiopia - Block, Paul J.; Strzepek, Kenneth M.; Rosegrant, Mark W.; Diao, Xinshen (Wiley, 2008)
Extreme interannual variability of precipitation within Ethiopia is not uncommon, inducing droughts or floods and often creating serious repercussions on agricultural and nonagricultural commodities. A dynamic climate module is integrated into an economy‐wide model containing a detailed zonal level agricultural structure. This coupled climate‐economic model is used to evaluate the effects of climate variability on prospective irrigation and infrastructure investment strategies, and the ensuing country‐wide economy. The linkages between the dynamic climate module and the economic model are created by the introduction of a climate‐yield factor (CYF), defined at the crop level and varied across Ethiopian zones. Nine sets of variable climate (VC) data are processed by the coupled model, generating stochastic wet and dry shocks, producing an ensemble of potential economic prediction indicators. Analysis of gross domestic product and poverty rate reveal a significant overestimation of the country's future welfare under all investment strategies when climate variability is ignored. The coupled model ensemble is further utilized for risk assessment to guide Ethiopian policy and planning.